Audit of training programs for students of legal accounting according to the International Accounting Education Standard (IES 5) Applied study at the Higher Institute of Accounting and Financial studies/University of Baghdad - Mowaffaq Abdul Hussain Mohammed; Ahmed Khaled Mahmood (Journal of Madenat Alelem University College, 2020)
Training programs are one of the foundations on which scientific and professional competencies are built in accounting disciplines to be able to measure and communicate economic events and provide appropriate information for decision making. Therefore, the international education standards board (IEASB) of the international federation of accountants (IFAC) has issued international standards combining the most important aspects of building the capacity of accountants and providing them with the requisite knowledge and skills, which results in the end result in the accounting and auditing professions qualified and trained scientifically and practically to lead the economic units efficiently and effectively, ensuring the achievement of quality and upgrading in the development of training programs implemented by institutions dealing with accounting education. The research has reached a range of conclusions, the most important of which is that the training programs applied at the institute for the four stages of study are fully applied and (65%) requirements of the international accounting education standard (IES 5) experience and practical training, while partially applied (23%) not applicable (12%). The research was presented to a set of recommendations, the most important of which is the need to rely on the paragraphs of the international accounting education standard (ies 5) experience and practical training and to benefit from it in the preparation and development of training programs for specialization of charted accounting and to ensure the efficiency in the scientific and practical qualification of students and achieve compatibility between theoretical study and practical application.